ROLE AND TASKS OF THE POLICE IN AN AIRPORT CRISIS SITUATION - Jerzy UCHROŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The article presented below refers to a crisis situation connected with a threat to public order in a public utility facility, such as an airport. The article presents the role and tasks of the police in releasing such a facility occupied by unauthorized people. An attempt to explain the basic concepts related to this issue has been made and the procedure, conditions and legal basis of the police intervention in conducting such an operation have been presented.